An Experimental Investigation on the Effect of Calcium Chloride As Dust Suppressant on the Strength of Unpaved Road - Al Bargi, Walid Abdullah; Ali Khalifa, Nasradeen; David Daniel, Basil; Md. Rohani, Munzilah; Oluwasegun Samuel Odebiyi, Oluwasegun Samuel Odebiyi (uthm, 2023)
The quality of the gravel used in road construction has a profound positive impact on road service life. The potential use of calcium chloride as a dust control agent and material for stabilizing the base of unpaved roads has been researched. However, the quality of the gravel may be impacted if calcium chloride is introduced as a dust suppressant into it. The main aim of this research is to examine the increase in strength of soil specimens treated with calcium chloride and to evaluate how different proportions of calcium chloride as a dust suppressant and base stabilizer affect the California Bearing Ratio value of the soil samples. Mixtures of natural gravel and gravel with varying amounts of calcium chloride were analyzed for their Atterberg limits, grading, maximum dry density, CBR properties, and optimum moisture content. The changes in the characteristics of the gravel - calcium chloride mixtures were analyzed. It was found that the particle size distribution and Atterberg limits remained largely unchanged. However, the optimum moisture content (OMC) decreased from 9.2% to 7.6%, 7.4%, and 7.2% with calcium chloride added at percentages of 2 percent, 3 percent, and 4 percent per volume of dry soil, respectively. Observation of the mixture revealed an increase in the maximum dry density (MDD) as the ratios of calcium chloride were altered. The maximum dry density significantly increased from 2.15 Mg / m3 to 2.31 Mg/m3 , 2.35 Mg/m3 , and 2.36 Mg/m3 , respectively. Along with this, the California Bearing Ratio (CBR) demonstrated an improvement of 25% to 29%, 32%, and 36% at 95% compaction with an increase in the ratios of calcium chloride. The increase in dry density can be explained by the improved bonding between particles and the reduction of air voids. This increase in dry density, in turn, positively influences the California Bearing Ratio by transforming soil structure from a dispersed state to a flocculated state. It can be inferred from the results that calcium chloride has the potential to function as a stabilizer for unpaved roads. The findings of this study are expected to reduced life cycle costs for unpaved roads, provide insights for the best approach to materials analysis for unpaved roads, and contribute to environmental benefits by minimizing dust emissions into the atmosphere and reducing the release of chemicals into nature.